ANALYSIS OF THE RELATIONSHIP OF DIET PATTERNS WITH THE INCIDENT OF HYPERTENSION IN THE COASTAL AREA OF THE WAKATOBI BAJO TRIBE - Hardi, Hardi; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Hypertension is often known as a non-communicable disease that can cause complications such as stroke and heart disease. Communities that have a coastal environment will have an influence on the culture of food processing and consumption patterns of people who tend to only consume seafood). The majority of people have a high-risk lifestyle and experience hypertension. People's lifestyles that have a high risk of developing hypertension are uncontrolled eating patterns, lack of exercise, active smoking and consuming alcoholic drinks as well as low correct knowledge about hypertension and low motivation to carry out health checks at health services or health centers. The aim of the research is to determine the relationship between patterns and the incidence of hypertension in the coastal area of the Bajo Wakatobi tribe. The method used in writing this literature review begins with selecting a topic, then determining keywords for journal searches. Several journal review results show that there is a relationship between pattern analysis and the incidence of hypertension in the coastal area of the Bajo Wakatobi tribe. Some databases include Google Cendikia and Pubmed. The keywords used are 'Diet Pattern, Hypertension, Coastal. Suggestion: based on the research results, there is a need for education from the health service or health service providers to coastal communities about the dangers of hypertension and also education about maintaining a healthy lifestyle to avoid hypertension. keywords : Coastal, Diet, Hypertension